New taxa of Alternaria, Cladosporium and Corynespora from North-eastern U.P., India - and D.K. AGRAWAL, RAGHVENDRA SINGH, SHAMBHU KUMAR, PALLAVI SHARMA, K. SHUKLA, KAMAL (Indian Phytopathology, 2008)
This communication deals with the descriptions and illustrations of hitherto undescribed species of phytopathogenic foliar hyphomycetes viz. Alternaria hydrophila R. Singh et al. sp.nov. on Nymphaea sp. (Nymphaeaceae), Cladosporium spinacearum R. Singh et al. sp.nov. on Spinacea oleracea (Amaranthaceae) and Corynespora ehreticola R. Singh et al. sp.nov. on Ehretia laevis (Ehretiaceae) respectively, are collected from Terai belt of North-Eastern U.P.. Type specimens have been deposited in H.C.I.O., New Delhi and their isotypes have been retained in the departmental herbarium for further reference. Morphotaxonomic determinations have been done by comparing with allied taxa in question and consulting the current literature.